2020
DOI: 10.18805/ijare.a-5426
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Character Association and Casual Relationship of Seed Yield and Its Components in Early Maturing Genotypes of Pigeon Pea (Cajanus cajan L.)

Abstract: The present investigation was undertaken with the objective to estimate the interrelationship of characters for seed yield in early maturing genotypes of pigeon pea (Cajanus cajan L.). The material consisted of twenty-one pigeon pea genotypes among which nineteen were early maturing genotypes received from ICRISAT (The International Crops Research Institute for the Semi-Arid Tropics), Hyderabad and two were local varieties collected from BNCA, AAU (Biswanath Chariali College of Agriculture, Assam Agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…These results clearly indicated that the selection based on these characters would directly improve the seed yield. These results were in conformity with that of Borah et al (2020), Alaka et al (2020) showed highest positive direct effect for biological yield followed by harvest index, days to maturity, seeds per pod and days to 50% flowering on grain yield per plant.…”
Section: Path Coefficient Analysissupporting
confidence: 89%
“…These results clearly indicated that the selection based on these characters would directly improve the seed yield. These results were in conformity with that of Borah et al (2020), Alaka et al (2020) showed highest positive direct effect for biological yield followed by harvest index, days to maturity, seeds per pod and days to 50% flowering on grain yield per plant.…”
Section: Path Coefficient Analysissupporting
confidence: 89%
“…Yield is a dependent character. It depends on various characters and environmental conditions that exist during crop growth (Borah et al, 2020). The protein content in cereal grains depends upon the genotype and environmental factors (Abdelaal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%